Bangkok May 2010 perspectives on a divided Thailand (Institute of Southeast Asian Studies, 2012)
After a two-month standoff between Red Shirt protestors and the government of Prime Minister Abhisit Vejjajiva, violence and arson scarred central Bangkok in mid-may 2010. This shocking turn of events underlined how poorly understood the deep divisions in the society and politics of Thailand remained, even five years into the country's prolonged crisis. This volume collects analysis and commentary on those divisions from an unusually large and prominent group of Thai and foreign scholars and observers of the country. Contributions examine socio-economic, political, diplomatic, historical, cultural, and ideological issues